2007
DOI: 10.3347/kjp.2007.45.4.295
|View full text |Cite
|
Sign up to set email alerts
|

Loss of infectivity of Neospora caninum oocysts maintained for a prolonged time

Abstract: Abstract:The purpose of this study was to investigate whether sporulated Neospora caninum oocysts, which had been stored for 46 mo in a 2% sulfuric acid solution at 4°C, remain morphologically viable and infective to gerbils (Meriones unguiculatus). Six gerbils were orally inoculated with doses of 400 or 1,200 oocysts. Two mo after inoculation, the animals did not show any clinical signs, had no histological lesions, and were seronegative for N. caninum at 1: 50 in an immunofluorescent antibody test. PCR using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…They are environmentally resistant like the oocysts of other coccidians (Uzeda et al, 2007;Neto et al, 2011).…”
Section: Definitive Hosts and Transmission By Oocystsmentioning
confidence: 98%
“…They are environmentally resistant like the oocysts of other coccidians (Uzeda et al, 2007;Neto et al, 2011).…”
Section: Definitive Hosts and Transmission By Oocystsmentioning
confidence: 98%
“…Aqueous 2% sulfuric acid has been commonly used to store N. caninum oocysts at 4 °C; how long oocysts remain viable under these conditions is not known. N. caninum oocysts remained viable for 108 days but not for 46 months when stored in 2% sulfuric acid at 4 °C (UZÊDA et al, 2007a). Recently, Fehlberg et al (2017) reported on successful development of a high resolution melting PCR method to distinguish Neospora, Sarcocystis and Toxoplasma using a single pair of primers targeting 18S rDNA.…”
Section: Environmental Resistance Of Oocystsmentioning
confidence: 99%
“…The aim of this study was to determine the presence of specific antibodies anti-N. caninum in samples from dogs and wild animals in a nature conservation area in the southeast of Portugal. Several serological techniques have been employed to screen for anti-N. caninum antibodies in different animal species, including the IFAT, usually using the cut-off of 1:50 in dogs (Björkman and Uggla, 1999;Silva et al 2007;Uzeda et al 2007;Yakhchali et al 2010;Robbe et al 2016;Wang et al 2016), the N-MAT and various ELISAs. The competitive cELISA and N-MAT are the most commonly used tests in wildlife, because these techniques do not require the use of species-specific secondary antibodies (Almería, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have also claimed that the IFAT is more specific than the ELISA, because the use of crude tachyzoite antigen as coating antigen in soluble extract-based ELISAs may be a cause of cross-reactivity with T. gondii and other related apicomplexan parasites (Björkman and Hemphill, 1998;Silva et al 2007). Though many authors consider the dilution 1:50 the most appropriate cut-off for seropositivity in dogs (Björkman and Uggla, 1999;Silva et al 2007;Uzeda et al 2007;Yakhchali et al 2010;Robbe et al 2016;Wang et al 2016), in this study, interpretation of results was difficult, with a high percentage of sera producing strong apical reactions, in many instances with incomplete peripheral fluorescence of fixed tachyzoites. Others, when using the IFAT for the serological screening of N. caninum in different species made similar observations (Paré et al 1995;Mineo et al 2001;Galvão et al 2015).…”
Section: Discussionmentioning
confidence: 99%